Strategi Dakwah Nahdlatul Ulama dan Muhammadiyah di Kabupaten Jepara dalam Perspektif Pemanfaatan Media Massa - Achmad Slamet; Aida Farichatul Laila (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2018)
The Nahdlatul Ulama and Muhammadiyah organizations are the two major organizations in Jepara. The success of this Islamic organization in da'wah can not be separated from the use of good da'wah strategy. A good strategy is supported by good means / media. From the number of da'wah media that can be used as syiar Islam, mass media is considered the most effective and efficient in the current era of technology. This research analyzes the strategy of mass media utilization in Islamic da'wah by two organizations; Nahdlatul Ulama and Muhammadiyah in Jepara District. This research uses the techniques of collecting up to data analysis that refers to qualitative research methodology, to find the data that answer the formulation of the problem that has been decided, about the comparison strategy of mass media utilization in daakwah between the two research objects. So the results of this study will culminate in the use of a number of comparative instruments to determine the similarities and differences, as well as the shortcomings and advantages of the two comparable research objects. After doing research with the data obtained can be concluded that the utilization of mass media used Islamic organization Nahdlatul Ulama in the most effective da'wah is through online media, while the Muhammadiyah organization the most effective use of mass media through print media such as magazine / bulletin. Whereas Equations and Differences. The equality of these two organizations in utilizing the mass media lies in the system of utilization; its own mass media management system and system of cooperation with other mass media. While the difference lies in the mass media products produced by these two Islamic organizations.